Russia and Venezuela: New Strategic Partnership in the Field of Response to Biological Threats and Prospects for Cooperation - V. V. Kutyrev; S. A. Shcherbakova; A. V. Ivanova; V. E. Kuklev; Zh. A. Kas’yan; I. G. Karnaukhov (Проблемы особо опасных инфекций)
The paper considers the key areas of international activities of the Federal Service for Surveillance on Consumers’ Rights Protection and Human Well-being in strengthening cooperation with specialized agencies of foreign countries in the global provision of sanitary-epidemiological welfare of the population at the current stage. Consistent work to strengthen the international network to counter emergency situations of a sanitary and epidemiological nature through effective interaction in the field of rapid response with partner countries in the near and far abroad, including through the organization of joint scientific and practical centers for the study and prevention of infectious diseases is presented. It is shown that the programs being implemented are aimed at strengthening the national healthcare structures of partner countries to achieve independence in the implementation of monitoring and anti-epidemic measures and building a single epidemiological space, independent of the influence of global and regional geopolitical fluctuations. The relevance of increasing interstate cooperation in the field of analysis and control of biological threats, primarily infectious diseases with the potential for emergencies of a sanitary and epidemiological nature of international concern, in the South American region is considered. The currently expanding strategic biosecurity collaboration with the Bolivarian Republic of Venezuela through the establishment of the first joint research center in the South American region is described. The first results of the joint work of Russian and Venezuelan specialists are presented, confirming the successful integration of Russian experience in monitoring and preventing biological threats into the system of ensuring the sanitary and epidemiological well-being of the Venezuelan population. Promising areas for further joint research are discussed.